Bronze 'bathtub' coffins in the context of 8th-6th century BC Babylonian, Assyrian and Elamite funerary practices - Wicks, Yasmina (Archaeopress archaeology., 2015)
This volume is dedicated to a small number of unique bronze 'bathtub' coffins found in 8th-6th century BC Babylonian, Assyrian and Elamite burial contexts. Usually treated as an incidental aspect of the burial process, these fascinating burial receptacles have until now garnered little in the way of academic interest. Here the author takes the opportunity to further explore the coffins, drawing together the widely dispersed information on their archaeological contexts, investigating the method and place of their manufacture, and establishing a possible date range for their production and use.